Editorial: Environmental Education and Educational Quality and Relevance- Opening the debate - Heila Lotz Sisitka (Environmental Association of Southern Africa, 2008)
This edition of the Southern African Journal of Environmental Education (SAJEE) tackles a critical issue being debated across the world today, namely the question of educational quality and relevance. In 2005 the UNESCO Education for All Global Monitoring Report entitled Education for All: The Quality Imperative (UNESCO, 2004) was published. This global monitoring report drew attention to issues of educational quality, and raised the problem that physical access to education does not necessarily lead to epistemological access to knowledge or to relevant education being offered to learners. In the foreword to the 430-page assessment of educational quality issues, Koïchiro Matsuura, Director General of UNESCO, stated that 'although much debate surrounds attempts to define educational quality, solid common ground exists ... Quality must be seen in light of how societies define the purpose of education' (UNESCO, 2004: Foreword). He went on to explain that there seem to be two mutually agreed upon purposes for education in the world today: cognitive development of learners, and creative and emotional growth of learners to help them acquire values and attitudes for responsible citizenship. He also pointed out that 'quality must pass the test of equity' (UNESCO, 2004: Foreword), emphasising the importance of equity of opportunity to access and participate in education and learning. Relevant to the field of environmental education, is the inclusion of educational quality as a major thrust of the United Nations Decade of Education for Sustainable Development (UNDESD) (UNESCO, 2004).